Teaching listening as a type of speech activity (Journal of Science-Innovative Research in Uzbekistan, 2024)
The article analyzes the issue of working with text at the initial, intermediate, and advanced stages of studying Russian as a foreign language. The relevance of the article is determined by the possible application of the research results to solve significant scientific and practical problems.